Don Cupitt: prophet, public intellectual and pioneer Public intellectual - Graham, Elaine L. (Theology, 2023)
The 1984 BBC TV series The Sea of Faith offered Don Cupitt an exceptional degree of public recognition and notoriety. His advancement of a non-realist and social constructivist theology had a strong polarizing effect on his audience, engendering disapproval and approbation in equal measure. Opinion was strongly divided between those who resisted any kind of critical approach to Christian teaching and those who felt liberated by Cupitt’s call for a more modern and questioning theology. Through archives of audience reactions to his broadcasts and writings, this article considers whether Cupitt’s influence through The Sea of Faith and other writing and broadcasting was sufficient to rank him as a ‘public intellectual’. It will argue that the controversy Cupitt attracted and his categorization as ‘atheist priest’ and ‘radical theologian’ may ultimately have limited his efforts to promote broad-based, serious theological debate in Church and society.